Pengujian Black Box ada Aplikasi Hitung Nilai Mahasiswa Menggunakan Metode Equivalence Partitions - Sri Mulyati; Irpan Kusyadi; Muhammad Iqbal Ashara; Prasetyo Adi Widodo; Wahyudin Wahyudin (Jurnal Informatika Universitas Pamulang, 2022)
Black-box testing is very influential in finding flaws and errors in the software because it can identify errors in functions, interfaces, data models, and access to external information sources. During the testing process, the problem often arises that the tester is never sure that the software being tested has met the criteria for being eligible for testing. This condition occurs because sometimes there are still some execution paths that have never been tested. The examiner should be able to make every possible mix of input information for the test material. The selection of input information to detect errors is a problem for testers because it has a high gap, so that an automatic test trial model can be a solution to automatically generate a test trial model in software testing. The black-box method with the identical division technique requires a false awareness technique.